General directions of interaction of the state bureau of investigations with public authorities - Frantsevych, Andrii (Actual problems of law (Aktual'ni problemi pravoznavstva), 2020)
The article examines the preconditions for the establishment of the State Bureau of Investigation. Emphasis is placed on activities related to the interaction of the State Bureau of Investigation with other public authorities. Scientific views on the formation of the concept of "interaction" are analyzed. The article establishes that one of the means of administrative and legal regulation of relations between the subjects of administrative law is interaction, coordination, coordination, agreement, administrative contract. Taking into account the scope of powers of the DBR and the tasks assigned to the bureau, based on the law, the main areas of cooperation with other government agencies are identified: 1) organization of pre-trial investigation of criminal offenses, resolution of other issues during criminal proceedings; 2) claims-claim direction; 3) exchange of operational information; 4) cooperation in the field of prevention and counteraction to legalization (laundering) of proceeds from crime and strengthening control over the use of funds from the State Budget of Ukraine; 5) interaction to identify facts of torture and ill-treatment of people; 6) for the organization of preventive measures in the fight against criminal offenses under the jurisdiction of the State Bureau of Investigation7) exchange of information. The implementation of each of these areas of interaction is analyzed, attention is focused on the regulations in which it is defined and enshrined. The need to take into account ways to promote the level of interaction, namely: the need to consolidate at the legislative level the concept of forms and boundaries of interaction between these subjects of pre-trial investigation; due to the lack of a single legal act regulating the interaction, it is necessary to introduce a single instruction on the organization and implementation of the interaction of law enforcement agencies, whose activities are related to the pre-trial investigation, etc.